64P Immune checkpoint inhibitors and tyrosine kinase inhibitors in patients with advanced hepatocellular carcinoma: Does the sequence matter?. (15th December 2019) - Lee, J; Ng, K; Wong, L; Ang, A; Tan, S H; Tai, D; Choo, S P
Abstract: Background: Tyrosine kinase inhibitors (TKI) are the first-line systemic treatment for patients with advanced hepatocellular carcinoma (HCC), while immune checkpoint inhibitors (ICI) were approved for use in the second-line setting in 2018. Results of phase III studies evaluating the role of first-line ICI use are pending. It is unknown if the sequencing of therapy of TKI and ICI makes a difference in response rate, nor if TKIs can be safely used in the third-line setting after ICI. Methods: Of 114 patients with advanced HCC treated with an ICI at our institution between 30 Dec 2013 and 13 Jun 2018, 59 who also received a TKI were retrospectively identified. Patients were classified into three categories: Group 1, those who had received TKI before an ICI (TKI1-ICI), Group 2 included those who received an ICI followed by an TKI (ICI-TKI2), and Group 3 included those who received a TKI both before and after ICI (TKI1-ICI-TKI2). Response evaluation was done based on RECIST v1.1. Results: 28 patients received TKI1-ICI, 24 received ICI-TKI2, and 7 received TKI1-ICI-TKI2. Median OS was 12.1, 13.9, 31.2m in groups 1, 2 and 3 respectively (p = 0.20), while PFS was 3.1, 2.1 and 3.7 m. (p = 0.40) Response rate to TKI was 3.6%, 12.5% and 28.6% respectively for Group 1, 2 and 3 (p = 0.10), and disease control rate was 21.4%, 25.0% and 71.4% respectively (p = 0.04). 65.7% of the patients who received TKI before ICI experienced adverse events of any grade, similar to 61.3% of patients who received TKI after ICI. The rate of grade 3 or higher adverse events were also similar at 5.8% and 9.7%. There were no grade 5 adverse events. Conclusion: DCR with TKI was higher when sequenced after ICI and even higher when sequenced after both prior TKI and ICI, suggesting that there may be a role for defining the sequence or combination of TKI and ICI in patients with HCC. No new safety signals were seen with use of TKI following ICI. Legal entity responsible for the study: Sing Health CIRB. Funding: Bayer. Disclosure: J. Lee: Advisory / Consultancy, Research grant / Funding (self): Bayer; Advisory / Consultancy: Ipsen. D. Tai: Research grant / Funding (self): Bristol-Myers Squibb; Research grant / Funding (self): Sirtex; Honoraria (self), Advisory / Consultancy: Bayer; Advisory / Consultancy: Ipsen; Advisory / Consultancy: Eisai. S.P. Choo: Advisory / Consultancy, Research grant / Funding (self): Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy: Lilly; Advisory / Consultancy, Research grant / Funding (self): Sirtex; Advisory / Consultancy: Novartis; Advisory / Consultancy: Eisai; Advisory / Consultancy: Bayer; Advisory / Consultancy: Celgene. All other authors have declared no conflicts of interest.